One summer : America, 1927 - Bryson, Bill (New York : Doubleday, 2013)
Bryson examines closely the events and personalities of the summer of 1927 when America's story was one of brawling adventure, reckless optimism and delirious energy
May : the Kid -- June : the Babe -- July : the President - - August : the anarchists -- September : summer's end
Includes bibliographical references (pages 469-480) and index
Keywords: Popular culture -- United States -- History -- 20th century; United States -- History -- 1919-1933; United States -- Social conditions -- 1918-1932; United States -- Social life and customs -- 1918-1945